Variasi Bahasa pada Deskripsi Singkat (Caption) Instagram Dosen Fakultas Tarbiyah IAI Al-Qolam Malang - Malikha, Usrin (JURNAL PUSAKA, 2022)
Based on research on language variations in the description of the Tarbiyah Faculty of IAI AL-Qolam Malang. So, it can be concluded that the research inludes language variations in terms of formality which are included in the types of official varietu, frozen variety, business variety, intimae style, and relaxed variety. Language variations in the use of Instagram social media esed by IAI Al-Qolam Malang Tarbiyah Faculty lecturers are language variations in terms of formality which fall into the types of business variety, relaxed variety ad intimate varoety. This can be seen from the words or sentences in the short description (caption) of the Instagram account of the Tarbiyah Faculty lecturer at IAI Al-Qolam Malang.